PKM PENINGKATAN PRODUKTIVITAS BERBASIS GREEN ECONOMY PADA COFFE SHOP KETANBA KOTA SURABAYA - Putra, Allen Pranata; Abdillah, Khubbi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
The condition of community service partners is the coffee shop "Ketanba" which has a location on Jl. Manyar Kerta Adi II Blok Y-135 No. 41. The priority problems of partners that will be tried to be solved are: 1) Production Field and 2) Marketing Field. Problem Solutions: 1) Assistance and training in food and beverage presentation; 2) Assistance and training on how to maintain the availability of raw materials so that they are not easily exhausted; 3) Assistance and training on product hygiene; 4) assistance and training in expanding market segmentation; 5) Assistance and training in online marketing optimization. Based on the objectives of the activities that will be carried out as follows: 1) Increase in the amount of production; 2) Increase the amount of partner turnover; 3) Expansion of market segmentation. The methods of implementing the Community Partnership Program are: 1) Training; and 2) Discussion. The results of PKM activities are: 1) The increase in production time is more precise and tends to be fast by 20%; 2) Increase in production of raw material availability by 60%; 3) Increase in partner cleanliness by 10%; 4) Increasing partner skills in serving and expanding market segmentation by 20%; and 5) An increase in online marketing by 20%.